Determinants of food security status of rural households living with HIV/AIDS in Southwestern Nigeria (2007)
The study assessed the determinants of food security status of households living with HIV /AIDS in Southwestern Nigeria. Eighty-five people living with HIV/AIDS were interviewed for the study, Descriptive statistics, cost of calorie measure and the Logit model were used in analyzing the data collected. The result shows that there is high prevalence of food insecurity among the households living with HIV /AIDS. The result of the Logit model also shows that gender, education, monthly food intake (Kcal), total monthly income, drug share and food share significantly influence the food security status of the households living with HIV/AIDS. To improve the food security status of households living with HIV/AIDS, it is recommended that economic policy should be directed towards the reduction of the food prices, thus reducing the food share of the household monthly expenditure